ENGLISH DEBATING AT AN ISLAMIC BOARDING SCHOOL: BEYOND SPEAKING SKILL AND CRITICAL THINKING - Atin Kurniawati (Universitas Islam Negeri Alauddin Makassar, 2022)
Plenty of studies have investigated English debating as a method to improve students’ speaking skill and critical thinking, whereas debating itself requires combination of several skills altogether from preparation to evaluation stage. Each stage in debating requires different skills. This study aims to shed some light on the influence of English debating activities on the progress of English skills and non-English skills of its members. Three students who joined the English debating club at an Islamic boarding school were involved in this study and they represented different length of membership. The data were collected through an open-ended questionnaire and followed by semi-structured interviews. The entire data collection stage was conducted online due to pandemic condition. The data were then coded and analysed using constant comparative method. This study revealed that English debating brought a good progress on both English skills and non-English skills of its members. Not only it improved the students’ speaking skill, but it also improved reading, listening, and writing skills. Along with the skills progress, they also confirmed much better vocabulary and grammar mastery. Non-English skills were also well-developed through English debating activities namely critical thinking, confidence, teamwork, and persistence. Team members interactions and coaching from the debating coach contributed a lot toward their progress. This study implies that English debating is suitable to develop all English skills as well as the students’ ability of critical thinking, teamwork, confidence, and persistence.